One Dark Night. - Wheeler, Lisa 1963- (New York, NY : Harcourt , Inc., 2003)
Mouse and mole feel afraid one dark night crossing a mush-mucky swamp and a marsh-misty meadow.
Keywords: Mice - Fiction; Moles (Animals) - Fiction; Fear - Fiction; Bears - Fiction; Friendship - Fiction; Stories in Rhyme; Bates, Irvin, ill